Effect of therapy on Quantiferon-Plus response in patients with active and latent tuberculosis infection - Petruccioli, Elisa; Chiacchio, Teresa; Vanini, Valentina; Cuzzi, Gilda; Codecasa, Luigi Ruffo; Ferrarese, Maurizio; Schininà, Vincenzo; Palmieri, Fabrizio; Ippolito, Giuseppe; Goletti, Delia (Scientific reports, 2018)
Lack of biomarkers for treatment monitoring is listed among the main requirements for next generation assays, as identified globally among tuberculosis (TB) researchers. In this study, we evaluated in a low TB endemic country such as Italy, the effect of preventive therapy on the results obtained in the QuantiFERON TB Plus (QFT-Plus), in a cohort of subjects with latent TB infection (LTBI) and active TB. We found that TB therapy significantly decreased IFN-γ values and number of responders to TB1- and TB2- peptides stimulation in both LTBI and active TB patients. Stratifying LTBI subjects according to the type of preventive TB therapy used, we found that INH treatment but not INH and RIF significantly decreased IFN-γ production. Stratifying the active TB patients according the microbiological status, we found that TB therapy significantly decreased IFN-γ response to antigen present in QFT-Plus test in patients with clinical diagnosis compared to those with a microbiological diagnosis. In conclusions, we demonstrated that TB therapy decreases IFN-γ level in response to antigen present in QFT-Plus test in LTBI and active TB patients. Future studies are needed to better characterize Mtb-specifc response as a potential marker for monitoring TB therapy and preventive treatment effects.